Evaluating the Mediation Role of Job Satisfaction on the Effect of Organizational Justice and Transformational Leadership on Organizational Commitment - Ezza Chairurrizqie; Siswoyo Haryono; Nuryakin Nuryakin (Universitas muhammadiyah malang, 2021)
The purpose of this study is to uncover the role of job satisfaction in mediating the effects of organizational justice and transformational leadership on organizational commitment. This study was carried out at Sumut Bank in Medan, Indonesia. Purposive sampling was used, with 200 questionnaires distributed. Organizational justice and transformational leadership have a good and significant effect on job satisfaction, according to the findings. Job satisfaction, on the other hand, has a positive and considerable impact on organizational commitment. Job satisfaction has little effect on organizational commitment when it comes to moderating the effects of organizational justice and transformational leadership. The key outcome of this study is that boosting transformational leadership, rather than enhancing organizational justice, will be more effective in increasing organizational commitment.